Temporal biological nitrogen fixation pattern in soybean inoculated with Bradyrhizobium. Issue 1 (5th August 2020) - Pitumpe Arachchige, Pavithra S.; Rosso, Luiz H. Moro; Hansel, Fernando D.; Ramundo, Bruce; Torres, Adalgisa R.; Asebedo, Ray; Ciampitti, Ignacio A.; Jagadish, S.V. Krishna
Abstract: Biological nitrogen fixation (BNF) in soybean [ Glycine max (L.) Merr.] plays an important role in sustainable agriculture, reducing the limitations associated with other sources of N such as fertilizers and soils. Our major objective was to evaluate the weekly pattern of BNF in soybean influenced by nodule formation, using three different laboratory‐cultured Bradyrhizobium strains. Plants were grown in 1‐m polyvinyl chloride (PVC) columns for 17 week in a greenhouse and BNF was determined using an integrated approach by assessing nodule formation, stem ureide‐N, and N partitioning in plant parts. Bradyrhizobium strains showed overall similar plant performance and N2 −fixation capacity. During the beginning of flowering/full bloom (R1/R2) growth stages, nodule formation significantly increased and reached a maximum at pod‐filling (R4) stage. Stem ureide‐N was detected at early growth stages even with fewer small nodules, which significantly increased after the beginning of pod formation (R3). Peak N2 −fixing rate (g N kg −1  d −1 ) started to decline after the onset of seed filling (R5.5). Relationship between BNF and nodule parameters (nodule number [ R 2  = .65] and nodule weight [ R 2  = .62]) suggested that they can be used as predictors of BNF.